4-Thiazolidinones: a novel class of hepatitis C virus NS5B polymerase inhibitors - KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (FRONTIERS IN BIOSCIENCE INC, 2008)
In a quest to identify novel compounds targeting HCV viral replicase, we evaluated a new series of 4-thiazolidinone derivatives (18 compounds). Our in vitro NS5B RdRp inhibition analysis with a series of 2', 4'-difluoro-4-hydroxybiphenyl- 3-carboxylic acid [2-(5-nitro-2- furyl/substituted phenyl)-4-thiazolidinone-3-yl] amides (1-7) yielded IC50 values ranging between 45-75 microM. Of these, lead compound 6: 2',4'-difluoro-4-hydroxybiphenyl-3-carboxylic acid[2-(2-fluorophenyl)-4-thiazolidinone- 3-yl] amide exhibited an IC50 value of 48 microM and inhibited NS5B non-competitively with respect to UTP and exhibited a mixed mode of inhibition with respect to RNA. Molecular docking of thiazolidinone derivatives within the allosteric site of NS5B yielded significant correlation between their calculated binding affinity and IC50 values. Taken together, these data suggest that the 4-thiazolidinone scaffold may be optimized for generating new analogues with improved anti-NS5B potency.
Keywords: HCV; NS5B; polymerase inhibitor; SARS; 4-thiazolidinone; kinetics; DEPENDENT RNA-POLYMERASE; NONSTRUCTURAL PROTEIN 5B; ESCHERICHIA-COLI; ALLOSTERIC INHIBITORS; BIOLOGICAL-ACTIVITY; ENRICHMENT FACTORS; SARS CORONAVIRUS; ACCURATE DOCKING; UNITED-STATES; DNA-SYNTHESIS